Combination of femoral triangle block and infiltration between the popliteal artery and the capsule of the posterior knee (iPACK) versus local infiltration analgesia for analgesia after anterior cruciate ligament reconstruction: a randomized controlled triple-blinded trial. Issue 9 (26th May 2021) - Martin, Robin; Kirkham, Kyle Robert; Ngo, Trieu Hoai Nam; Gonvers, Erin; Lambert, Jean; Albrecht, Eric
Abstract : Background and objectives: Femoral triangle block and local infiltration analgesia are two effective analgesic techniques after anterior cruciate ligament reconstruction. Recently, the iPACK block (infiltration between the popliteal artery and the capsule of the posterior knee) has been described to relieve posterior knee pain. This randomized controlled triple-blinded trial tested the hypothesis that the combination of femoral triangle block and iPACK provides superior analgesia to local infiltration analgesia after anterior cruciate ligament reconstruction. Methods: Sixty patients undergoing anterior cruciate ligament reconstruction received general anesthesia and were randomly allocated to two groups: femoral triangle block and iPACK under ultrasound guidance or local infiltration analgesia. For each group, a total of 160 mg of ropivacaine was injected. Postoperative pain treatment followed a predefined protocol with intravenous morphine patient-controlled analgesia, acetaminophen, and ibuprofen. The primary outcome was cumulative intravenous morphine consumption at 24 hours postoperatively. Secondary pain-related outcomes included pain scores (Numeric Rating Scale out of 10) measured at 2 and 24 hours postoperatively. Functional outcomes, such as range of motion and quadriceps strength, were also recorded at 24 postoperative hours, and at 4 and 8 postoperative months. Results: Cumulative intravenous morphine consumption at 24 hours postoperatively was significantly reduced in the femoral triangle block and iPACK group (femoral triangle block and iPACK: 9.7 mg (95% CI: 6.7 to 12.7); local infiltration analgesia: 17.0 mg (95% CI: 11.1 to 23.0), p=0.03). Other pain-related and functional-related outcomes were similar between groups. Conclusions: The combination of femoral triangle block and iPACK reduces intravenous morphine consumption during the first 24 hours after anterior cruciate ligament reconstruction, when compared with local infiltration analgesia, without effect on other pain-related, early, or late functional-related outcomes. Trial registration number: ClinicalTrials.gov Registry (NCT03680716 ).